AUDIT SISTEM INFORMASI INSTALASI RAWAT INAP PADA RUMAH SAKIT ISLAM JEMURSARI SURABAYA BERDASARKAN COBIT 4.1 - Sudarmadji, Anggy Pranindya; Sutomo, Erwin; Wardhanie, Ayouvi Poerna (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2018)
Jemursari Islamic Hospital has a hospital management information system (SIMRS) in 2013 until now. Inpatient installation information system is a system of admission, hospitalization to hospital. It will be slow, from the beginning of SIMRS implementation until now there are still problems found in the implementation of SIMRS. The problem is the service process that still exists a few stages long, inpatient services in the way available still requires more than 15 minutes have been using information systems, incompatibility of inpatient data with the system, mismatch manual manual report on the system and the nonconformity of the class ordered by the patient with the initial order and the patient's information about the medical record. Therefore, to overcome the problem above the solution is to conduct an information system audit at Jemursari Islamic Hospital of Surabaya by using COBIT 4.1 method. COBIT 4.1 method there are 4 stages of planning, preparation, implementation and reporting audit. Four stages produce a solution of a hospital management information system (SIMRS) and results for this information. The final value of the information system is 3.91 which has a manageable and scalable meaning.